Strategi Pengelolaan Zakat di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Seluma - Epen Triansah; Desi Isnaini; Badaruddin Nurhab (Economic Reviews Journal, 2025)
This research analyzes the zakat management strategy at BAZNAS Seluma Regency in increasing the effectiveness and efficiency of zakat collection and distribution to mustahik. Data was collected through observation, interviews and documentation guided by a list of questions. The analysis results show that: 1). The strategies of Baznas Seiluima Regency in collecting zakat funds are: short-term programs, medium-term programs and long-term programs. 2). The zakat management strategy in Baznas Seiluima Regency is as follows: 1). Management planning, 2). Mustahik identification, 3). Distribution, 4). Supervision of zakat management, and 5). Evaluation of zakat management.